Collaboration visit of the nuclear medicine team from Universitas Padjadjaran, Indonesia to Universiti Teknologi MARA / Muhamad Faiz Othman - Othman, Muhamad Faiz (Faculty of Pharmacy, 2024)
On April 18, 2024, a delegation from Universitas Padjadjaran, Indonesia, visited the Faculty of Pharmacy at Universiti Teknologi MARA (UiTM). The delegation comprised five distinguished researchers: Professor A. Hussein S. Kartamihardja, Associate Professor Dr. Holis Abdul Holik, Dr. Arifudin Achmad, Dr. Kharisma Perdani K., and Dr. Neneng Elly Rosilawaty. Representing both the Faculty of Medicine and the Faculty of Pharmacy of Universitas Padjadjaran, the team arrived at 10 a.m. and was formally received by Dr. Norkasihan Ibrahim, Deputy Dean of Industry, Community, Alumni, and Networking (ICAN), and Dr. Muhamad Faiz Othman.